2012
DOI: 10.1093/annonc/mdr384
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection assessed by ELISA and by immunoblot and noncardia gastric cancer risk in a prospective study: the Eurgast-EPIC project

Abstract: Using a western blot assay, nearly all noncardia GC were classified as H. pylori positive and the OR was more than threefold higher than the OR assessed by ELISA, supporting the hypothesis that H. pylori infection is a necessary condition for noncardia GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 18 publications
2
89
0
1
Order By: Relevance
“…Serology of H. pylori was available for 43 of the 48 GC cases, being positive for 41 of them, but was not available for the subcohort. However, a recent study (30) suggests that H. pylori infection is a necessary condition for gastric carcinogenesis and, therefore, adjustment or stratified analysis by H. pylori would be uninformative, at least for noncardia GC. In addition to potential confounders we also investigated the effect according to levels of the potential sources of DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…Serology of H. pylori was available for 43 of the 48 GC cases, being positive for 41 of them, but was not available for the subcohort. However, a recent study (30) suggests that H. pylori infection is a necessary condition for gastric carcinogenesis and, therefore, adjustment or stratified analysis by H. pylori would be uninformative, at least for noncardia GC. In addition to potential confounders we also investigated the effect according to levels of the potential sources of DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, some authors looked at CagA antibodies that are supposed to persist for longer periods of time after curing the infection by antibiotic treatment, or spontaneous clearance during the progression of atrophy. In a nested European case-control study from the Eurogast-EPIC project, Gonzalez et al [12] showed by using immunoblot detecting CagA antibodies that nearly, all noncardia-gastric cancer cases were indeed H. pylori positive, with an odds ratio three times higher than that obtained by ELISA.…”
Section: Epidemiologymentioning
confidence: 99%
“…In point of fact, bias due to the differences in the methods used to detect HP and a systemic and substantial under-detection of Helicobacter pylori infection and underestimation of its effect on gastric cancer is at the end not excluded. (Nomura et al, 1991) 1991 USA 295 92 109 111 186 Nomura et al (Parsonnet et al, 1991) 1991 USA 218 103 109 83 109 Uemura et al (Uemura et al, 2001) 2001 Japan 1526 36 36 1210 1490 Miki (Miki 2011) 2011 Japan 5290 59 63 4151 5227 González et al (González et al, 2012) …”
Section: The Data Of the Studies Analyzedmentioning
confidence: 99%